Yield of Brain Magnetic Resonance Imaging in Epilepsy Diagnosis from 1998 to 2020: A Large Retrospective Cohort Study - Stern, Tomer; Kornreich, Liora; Goldberg, Hadassa (Neuropediatrics, 2021)
Background We aimed to find the clinical significance of brain abnormalities on magnetic resonance imaging (MRI) in epilepsy and the lateralization of these findings with electroencephalogram (EEG).Methods We retrospectively analyzed the results of all EEGs and brain MRIs of 600 consecutive epilepsy patients from 1998 to 2020.Results Data were available for 563 cases (267 females). Ninety percent of the patients were 18 years old or younger. A total of 345 patients (61.3%) had focal epilepsy, 180 (32%), generalized, and 38 (6.7%), inconclusive. In 187 (33.2%), the first MRI was abnormal and in 81 (out of 108 repeated MRI), the second was pathological. The most frequent brain abnormalities were cortical dysplasia in 41 (18.1%), other structural abnormalities in 25 (11%), various phacomatoses in 23 (10.1%), and mesial temporal sclerosis in 17 (7.5%). Among 226 patients with abnormal MRI, 171 (75.6%) had focal epilepsy when compared with 36 (15.9%) with generalized epilepsy (p <0.001). In 121 patients (53.5%), the result of the abnormal MRI contributed significantly to the understanding of the epilepsy etiology. The side of abnormality was lateralized to the EEG focus in 120 cases (53%); in 10/15 cases with infantile spasms (66%), MRI was significantly abnormal. In 33, in whom the first MRI was normal, a second MRI revealed a significant abnormality.Conclusion Brain MRI is an important tool in epilepsy diagnosis, mainly in focal seizures and infantile spasms. A repeat MRI is mandatory in intractable focal cases to improve the yield of this test.
Keywords: epilepsy diagnosis; brain MRI; EEG; clinical significance; semiology